Kekosongan Hukum terhadap Pemain Judi Online dalam Sistem Hukum Positif Indonesia: Kajian atas KUHP dan Undang-Undang ITE - Hilmy, Ahmad Syaikhan; Jadidah, Fikrotul (Postulat, 2026)
Article 28F of the 1945 Constitution of the Republic of Indonesia recognizes human rights in the form of the right to communicate and obtain information. Nowadays, this right is often exercised through social media. However, the intended positive and healthy environment of social media is increasingly being tainted by the rise of online gambling. Existing regulations have proven insufficient in providing legal justice, certainty, and utility. In addition, the legal and social impacts within society tend to be harmful and misaligned with the spirit of eradicating online gambling crimes. This research employs a normative legal method with a statutory approach. The findings indicate a legal vacuum in regulating online gambling for personal use by individual players. Therefore, this study encourages the strengthening of the task force for combating online gambling and advocates for the establishment of more specific, comprehensive, and implementable regulations addressing individual online gambling practices.